Concordance between Lactose Quick Test, hydrogen‐methane breath test and genotyping for the diagnosis of lactose malabsorption in children. Issue 5 (21st December 2017) - Rojo, C.; Jaime, F.; Azócar, L.; Hernández, C.; Villagrán, A.; Miquel, J. F.; Arancibia, G.
Abstract: Background: Lactose intolerance is a frequent condition in certain populations. Different methods for diagnosis exist. There is scarce literature regarding Lactose Quick Test (LQT) and concordance with other methods for lactose intolerance diagnosis in children. Methods: Prospectively, we included children who underwent gastroduodenoscopy for evaluation of abdominal pain. We obtained a duodenal sample for LQT and blood sample for genetic test to evaluate LCT C>T‐13910 variant. Later, patients underwent breath test with lactose, to evaluate malabsorption. We evaluated the concordance between the three different tests. Key Results: We included 46 patients, 56.5% women. Mean age was 13.2 years (range 9‐18 years). 66.6% of patients had lactose malabsorption according to breath test; 64.4% were homozygous CC; and 91.3% had hypolactasia (mild or severe) according to LQT. None of the patients with normolactasia had altered breath test. Genetic test had a substantial agreement ( k  = 0.675) with breath test and fair agreement ( k  = 0.301) with LQT. LQT had fair agreement ( k  = 0.348) with breath test. Conclusions & Inferences: Genetic test had better concordance with breath test than LQT to diagnose lactose malabsorption, however, none of the patients with normal LQT had lactose malabsorption. In patients who undergo gastroduodenoscopy to study abdominal pain, it seems reasonable to perform LQT, and, in those with hypolactasia, to perform breath test. Abstract : In our study, we found a high diagnostic concordance between the genetic test and the breath test with lactose, and lower concordance with LQT. However, in none of the patients with normolactasia by LQT, the breath test was abnormal.